CXCL14 is a candidate biomarker for Hedgehog signalling in idiopathic pulmonary fibrosis. Issue 9 (1st March 2017) - Jia, Guiquan; Chandriani, Sanjay; Abbas, Alexander R; DePianto, Daryle J; N'Diaye, Elsa N; Yaylaoglu, Murat B; Moore, Heather M; Peng, Ivan; DeVoss, Jason; Collard, Harold R; Wolters, Paul J; Egen, Jackson G; et al.
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is associated with aberrant expression of developmental pathways, including Hedgehog (Hh). As Hh signalling contributes to multiple pro-fibrotic processes, Hh inhibition may represent a therapeutic option for IPF. However, no non-invasive biomarkers are available to monitor lung Hh activity. Methods: We assessed gene and protein expression in IPF and control lung biopsies, mouse lung, fibroblasts stimulated in vitro with sonic hedgehog (SHh), and plasma in IPF patients versus controls, and cancer patients before and after treatment with vismodegib, a Hh inhibitor. Results: Lung tissue from IPF patients exhibited significantly greater expression of Hh-related genes versus controls. The gene most significantly upregulated in both IPF lung biopsies and fibroblasts stimulated in vitro with SHh was CXCL14, which encodes a soluble secreted chemokine whose expression is inhibited in vitro by the addition of vismodegib. CXCL14 expression was induced by SHh overexpression in mouse lung. Circulating CXCL14 protein levels were significantly higher in plasma from IPF patients than controls. In cancer patients, circulating CXCL14 levels were significantly reduced upon vismodegib treatment. Conclusions: CXCL14 is a systemic biomarker that could be used to identify IPF patients with increased Hh pathway activity and monitor the pharmacodynamic effects of Hh antagonist therapy in IPF. Trial registration number: Post-results, NCT00968981 .